Scope of Nurse Led Preventive Oncology Clinic in India - Mathew Varghese V.; Sneha Sara Sam (International Journal of Oncological Nursing and Practices, 2023)
India holds immense potential and a promising future for the extensive implementation of nurse-led preventive oncology clinics, considering its substantial burden of cancer-related morbidity and mortality. The healthcare system in India is not equipped enough to cater to the growing needs of the population, and there is a lack of preventive services, particularly for cancer. In this context, nurse-led preventive oncology clinics can play a pivotal role in addressing the unmet needs of the population. Nurse-led preventive oncology clinics can provide essential services such as cancer screening, early detection, education, counseling, and follow-up care. Nurses are well placed to lead such clinics as they have the necessary skills and knowledge to provide comprehensive care to patients with cancer. Additionally, these clinics have the capacity to deliver patient-centered care, addressing the unique requirements of each patient, which ultimately improves patient satisfaction and overall outcomes. Furthermore, nurse-led preventive oncology clinics play a vital role in connecting the community with the healthcare system, closing the existing gap. They can work with community leaders and stakeholders to increase awareness about cancer prevention and the importance of screening. Furthermore, nurses can engage in collaborative efforts with other healthcare practitioners, fostering a coordinated approach to cancer care. Introducing nurse-led preventive oncology clinics in India has the potential to bring about a noteworthy decrease in the impact of cancer-related illness and death. Additionally, these clinics can contribute to reducing the financial burden associated with cancer treatment in healthcare expenditures. Moreover, they can provide employment opportunities for nurses and contribute to the overall development of the healthcare system in India. However, the implementation of nurse-led preventive oncology clinics in India also faces some challenges. The lack of resources, infrastructure, and trained personnel can pose a significant challenge. Moreover, there is a need for policy support and funding to ensure the sustainability of these clinics. In conclusion, nurse-led preventive oncology clinics have a significant role to play in addressing the unmet needs of the population in India. The implementation of these clinics can lead to better patient outcomes, increased awareness about cancer prevention, and overall development of the healthcare system in India. By garnering support from policymakers, stakeholders, and the community, it is possible to surmount the challenges at hand.
Keywords: Nurse led clinic; cancer prevention; cancer screening; preventive oncology clinic; scope and challenges